2010
DOI: 10.1007/s11010-010-0612-5
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial fibrosis and TGFB expression in hyperhomocysteinemic rats

Abstract: Hyperhomocysteinemia, characterized by an elevated plasma homocysteine concentration, leads to several clinical manifestations and particularly cardiovascular diseases. Experimental models of hyperhomocysteinemia revealed several tissue injuries including heart fibrosis and ventricular hypertrophy. In order to analyze the molecular mechanisms link to these morphological alterations, a mild hyperhomocysteinemia was induced in rats via a chronic methionine administration. Effects of methionine administration wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 39 publications
5
25
1
1
Order By: Relevance
“…Activated TGF- β 1 can induce myofibroblast formation and increase extracellular matrix deposition by upregulating collagen synthesis and inhibiting matrix degradation, which leads to myocardial fibrosis 23) . In addition, NF- κ B and JNK pathways can be activated by Hcy 7, 44) . Here, we found that IMD 1–53 inhibited the Hcy-increased levels of inflammatory molecules such as TNF- α , MCP-1, IL-6, and IL-1 β in the ApoE-/- mouse myocardium treated with Hcy, which was further confirmed in CFs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activated TGF- β 1 can induce myofibroblast formation and increase extracellular matrix deposition by upregulating collagen synthesis and inhibiting matrix degradation, which leads to myocardial fibrosis 23) . In addition, NF- κ B and JNK pathways can be activated by Hcy 7, 44) . Here, we found that IMD 1–53 inhibited the Hcy-increased levels of inflammatory molecules such as TNF- α , MCP-1, IL-6, and IL-1 β in the ApoE-/- mouse myocardium treated with Hcy, which was further confirmed in CFs.…”
Section: Discussionmentioning
confidence: 99%
“…Hcy is an amino acid-containing sulfydryl from methionine. The normal concentration of circulating Hcy is approximately 10 µmol/l, while the level of Hcy in hyperhomocysteinemia (HHcy) exceeds 15 µmol/l 7) . Plasma Hcy level was closely relative to left ventricular myocardial hypertrophy and left ventricle mass fraction 8, 9) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mild hyperhomocysteinemia induced in rats via chronic methionine administration or in heterozygous cystathionine--synthase (Cbs) deficient mice induces cardiomyocyte hypertrophy and interstitial fibrosis [9,10]. However, an analysis of in vivo cardiac function has not been performed in these models.…”
Section: Introductionmentioning
confidence: 99%
“…Mild hyperhomocysteinemia, characterized by an elevated plasma Hcy concentration between 15 and 30 lmol/L (Raaf et al, 2011), is common in many populations whereas can be caused by thermolabile variant of methylenetetrahydrofolate reductase, vitamin deficiencies, drug treatment, aging, smoking, alcohol consumption, or can be secondary to systemic diseases such as insulin-dependent diabetes and hypothyroidism (Jacques et al, 2001;De Bree et al, 2002;Castro et al, 2006;Selhub, 2006;Troen et al, 2008). Furthermore, studies have shown that mild hyperhomocysteinemia is a risk factor to cardiovascular (De Bree et al, 2002;Huang et al, 2008) and neurodegenerative diseases (Obeid and Herrmann, 2006;Minagawa et al, 2010;Herrmann and Obeid, 2011).…”
Section: Introductionmentioning
confidence: 99%